Ovarian Steroid Cell Tumor, NOS Presenting with Massive Ascites and Elevated CA-125 - Layla S. Abdullah (Journal of King Abdulaziz University: Medical Sciences, 2023)
Steroid cell tumors, not otherwise specified, are rare and usually benign. Ovarian sex cord stromal tumors of the ovary presenting with virulization in middle age women (average age: 43) are reported. Rarely, these tumors occur in postmenopausal women and, even more seldom, show a malignant clinical behavior. Although excess androgen secretion with virtualization is usually the primary presenting symptoms, rarely patients with this tumor present primarily with ascites. An unusual case was reported of a postmenopausal woman with a malignant steroid cell tumor, NOS, who was diagnosed with sudden onset of massive ascites as the primary clinical presentation. Aspects of clinical and pathologic findings as well as management pathways are introduced.